Long-term results of the Polish Adult Leukemia Group PALG-CLL2 phase III randomized study comparing cladribine-based combinations in chronic lymphocytic leukemia. Issue 3 (March 2014) - Robak, Tadeusz; Blonski, Jerzy Z.; Gora-Tybor, Joanna; Calbecka, Malgorzata; Dwilewicz-Trojaczek, Jadwiga; Boguradzki, Piotr; Dmoszynska, Anna; Kowal, Malgorzata; Kloczko, Janusz; Piszcz, Jaroslaw; Stella-Holowiecka, Beata; Sulek, Kazimierz; et al.
Abstract Long-term outcomes following newer therapies for chronic lymphocytic leukemia (CLL) have rarely been reported. This article presents the results of the final analysis of the Polish Adult Leukemia Group PALG-CLL2 study performed 10 years from final patient enrollment. With the extended follow-up time, it was found that cladribine (2-CdA)-based combinations CMC (2-CdA, cyclophosphamide, mitoxantrone) and CC (2-CdA, cyclophosphamide) administered as first-line treatment of progressive CLL resulted in significantly longer progression-free survival, but similar overall survival compared to 2-CdA monotherapy. Furthermore, the risk of potentially fatal late adverse events including infections, autoimmune complications and, particularly, secondary neoplasms was comparable among patients treated with CMC, CC or 2-CdA. The results of our analysis support the importance of long-term outcome monitoring of randomized trials in CLL.